Design and fabrication of an automatic fish feeding system for home aquarium - Siti Aisyah, Saahri (2015)
This project is devoted to design and fabricate an automatic fish feeding system for the application of home aquarium. An automatic fish feeder is a device that will dispenses fish food at a predetermined time and with selected amount. This automatic fish feeder is a solution for aquarist to ensure their pet fishes are fed in healthy way and on schedule. The project implements the integration of mechanical and electrical/electronic system to control fish feeding operation. The controller used for this device Arduino Uno microcontroller board. The controller controls the feeding mechanism and feedback system. This device uses a vertical screw conveyor mechanism to dispense the fish food into the water. The mechanism is actuated by unipolar stepper motor where the amount of dispensed food is controlled by the motor steps input when it is coupled to the screw conveyor. On the other hand, the feedback system is consist of user interface feature using keypad button for aquarist to choose the amount of dispensed food and infrared sensor as a warning system to warn aquarist when fish food level is low. A brief literature review is made on all of the elements involved in this system such as Arduino Uno microcontroller, stepper motor, screw conveyor, sensor and user interface feature. At the end of this project the automatic fish feeding system is successfully designed and fabricated following the specified objectives.